2010
DOI: 10.1093/mp/ssq014
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Inheritance and Resetting of Stress-Induced Loss of Epigenetic Gene Silencing in Arabidopsis

Abstract: Plants, as sessile organisms, need to sense and adapt to heterogeneous environments and have developed sophisticated responses by changing their cellular physiology, gene regulation, and genome stability. Recent work demonstrated heritable stress effects on the control of genome stability in plants—a phenomenon that was suggested to be of epigenetic nature. Here, we show that temperature and UV-B stress cause immediate and heritable changes in the epigenetic control of a silent reporter gene in Arabidopsis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
199
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(220 citation statements)
references
References 50 publications
10
199
1
3
Order By: Relevance
“…For instance, it was shown that abiotic stress can cause the release of transgene silencing and the reactivation of endogenous heterochromatic loci in Arabidopsis (Lang-Mladek et al 2010;Pecinka et al 2010;TittelElmer et al 2010). Interestingly, this stress-mediated transcriptional activation is not associated with DNA demethylation or changes in repressive histone modifications, two epigenetic marks that are characteristic for the release of transcriptional gene silencing (Lang-Mladek et al 2010;Pecinka et al 2010;Tittel-Elmer et al 2010). Instead, heat stress led to a dramatic reduction in nucleosome loading and affected chromatin organization (Pecinka et al 2010).…”
Section: Epigenetic Stress Responses and Their Potential Inheritancementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it was shown that abiotic stress can cause the release of transgene silencing and the reactivation of endogenous heterochromatic loci in Arabidopsis (Lang-Mladek et al 2010;Pecinka et al 2010;TittelElmer et al 2010). Interestingly, this stress-mediated transcriptional activation is not associated with DNA demethylation or changes in repressive histone modifications, two epigenetic marks that are characteristic for the release of transcriptional gene silencing (Lang-Mladek et al 2010;Pecinka et al 2010;Tittel-Elmer et al 2010). Instead, heat stress led to a dramatic reduction in nucleosome loading and affected chromatin organization (Pecinka et al 2010).…”
Section: Epigenetic Stress Responses and Their Potential Inheritancementioning
confidence: 99%
“…Such epialleles contribute to the phenotypic diversity of a population and, hence, may have a role in adaptation and evolution. Moreover, the formation of certain epialleles may be triggered by the environment, as suggested in several recent plant studies (Molinier et al 2006;Hauben et al 2009;Boyko et al 2010;Kathiria et al 2010;Lang-Mladek et al 2010;Verhoeven and van Gurp 2012). If such effects last for several generations, the modern evolutionary synthesis will have to be expanded.…”
mentioning
confidence: 99%
“…The first evidence that epigenetic marks could indeed be inherited across more than one generation involved transgenes (Allen et al, 1990, Sapienza et al, 1987, Swain et al, 1987. More recently, Lang-Mladek et al, showed in plants that, after extreme temperature or UV-B stress, a silent transgene and several transposable elements were activated, and these changes were heritable for two generations (Lang-Mladek et al, 2010). This suggests that some epigenetic marks may avoid erasure during early development, including the germ line.…”
Section: Epigenetic Memory and Inheritancementioning
confidence: 99%
“…Environmental factors can influence epigenetic processes, and may therefore be related to cancer development (Brait et al, 2009, Lang-Mladek et al, 2010. There are indications that endogenous factors such as the hormonal balance between estrogens and androgens might play a role (Godmann et al, 2009).…”
Section: Environmental Factors In the Pathogenesis Of Gccmentioning
confidence: 99%
“…A possible mechanism via which the 2245 site could become differentially methylated may involve an interaction between the site and either small or lncRNAs. In plants, small (21-24 nt) RNAs are known to trigger epigenetic gene silencing (Lang-Mladek et al 2010;Hauser et al 2011). The cly1 locus includes four sites, including the 2245 site, which could in principle be targeted by siRNAs ( Figure 5A).…”
mentioning
confidence: 99%